Bullying Victimization, Coping Strategies, and Depression of Children of China - Xie, Shenghua (Journal of interpersonal violence, 2022)
It is common knowledge that bullying victimization and coping strategies significantly affect the psychological well-being of children. However, which coping strategies are more effective at a particular level of bullying victimization is underexplored. Using survey data from 1,634 children from 10 schools in Wuhan, China, this study aims to investigate the abovementioned research gap. The results of factor analysis suggest that coping strategies of children in China can be divided into three types: help-seeking, avoidance, and self-defense. The results of multilevel modeling suggest that children adopting different coping strategies have distinct levels of depression. Help seekers show a significantly lower level of depression than self-defenders and avoiders. However, with increased bullying victimization, the effectiveness of the help-seeking strategy gradually decreases to offset the negative effect of bullying victimization on psychological well-being. Instead, those who adopt the self-defense strategy display a lower level of depression. The findings of this study suggest that there is no single coping strategy that is best for children, and the more effective strategy largely relies on the level of bullying victimization. The findings also imply that without external support, it is almost impossible for children to completely overcome the negative consequences of bullying on their own.